2015
DOI: 10.4081/oncol.2015.261
|View full text |Cite
|
Sign up to set email alerts
|

Rare cytogenetic abnormalities and alteration of microRNAs in acute myeloid leukemia and response to therapy

Abstract: Acute myeloid leukemia (AML) is the most common acute leukemia in adults, which is heterogeneous in terms of morphological, cytogenetic and clinical features. Cytogenetic abnormalities, including karyotype aberrations, gene mutations and gene expression abnormalities are the most important diagnostic tools in diagnosis, classification and prognosis in acute myeloid leukemias. Based on World Health Organization (WHO) classification, acute myeloid leukemias can be divided to four groups. Due to the heterogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Epigenetic changes such as chromatin modification, microRNA expression changes, and DNA methylation changes have been reported extensively in cancer studies. 4 The methylation pattern of CpG sites is an epigenetic regulator of gene expression. 5,6 Extensive alterations in DNA methylation have been noted in almost all cancer types, causing changes in gene expression that promote oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic changes such as chromatin modification, microRNA expression changes, and DNA methylation changes have been reported extensively in cancer studies. 4 The methylation pattern of CpG sites is an epigenetic regulator of gene expression. 5,6 Extensive alterations in DNA methylation have been noted in almost all cancer types, causing changes in gene expression that promote oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Acute myelocytic leukemia is prevalent among children and adults with a higher proportion in adults. The incidence also increases with the growth of age, and the maximum age of AML patients even reaches 60 years old [2]. In the clinical treatment of AML, it has been found that some AML patients in middle and old age achieved complete remission after treatment, while many more of these patients may face relatively high recurrence and a low survival rate [3].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small noncoding RNAs that downregulate the translation of target protein-coding mRNAs at the 3'-untranslated region (3'-UTR) (4). Accumulating evidence indicated that miRNAs enhance cancer cell proliferation, apoptosis and metastasis in solid tumors and leukemia (5)(6)(7)(8). Previous studies have also revealed that abnormal expression of miR-873 occurs in various types of cancer, such as breast, lung, colorectal and ovarian cancer, and glioma (9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%